Perilaku non linier dan mekanisme keruntuhan struktur konsol pendek (studi kasus struktur konsol pendek delat asi gedung program Diploma Teknik Sipil UGM) - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRACT Corbel structure is widely used to support beam in delatation and also to support crane structure. The partial failure is almost occurs on service time, that remark by crack like in corbel structure on diploma program of civil engineering UGM's building. Non linear analysis that widely used to investigate structural damage is used in this research. Research is done with the numerical finite element method implemented in A TENA program and by field experiment with hammer test tool. Structural modeling for numerical calculation is done by varying the dimension and supporting plate, and findin~ the crack pattern that mat~h with one on that delatation. . . .. . Partial fallure occurs on concrete IS caused by shear force whIch relatIvely hIgh "'tensIty caused by stress concentration due to not properly placed and small size of angle profile and in addition to not perfectly concrete casting that makes void on the concrete. This phenomenon can be seen from crack pattern that match by model with small bearing plate on A TENA program. From measurement by hammer test the front side of corbel has smallest compressive strength 15.9 MPa where crack occur, whereas the strongest area is at the bottom of the corbel of33.2 MPa. Keywords:perilaku non linear, struktur konsol pendek